PASAL 27 AYAT (3) UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DALAM PERSPEKTIF KEBEBASAN BERPENDAPAT - Demar Bunga Kinanti; Hufron Hufron; Syofyan Hadi (Sekolah Tinggi Pariwisata Mataram, 2022)
Article 7 of the Freedom of Opinion Law states that: “In the implementation of public expression of opinion by citizens, the apparatus is obliged and responsible for: (a). protect human rights; (b). respect the principle of legality; (c). respect the principle of the presumption of innocence; and D). organize. Furthermore, Article 8 of the Freedom of Opinion Law states that: